European Financial Integration and Revenue from Seignorage : The Case of Italy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
Financial integration is likely to entail EEC-wide convergence in both inflation rates and bank reserve requirements, thereby lowering some governments' seignorage revenues. These revenue losses, however, may be offset by concomitant effects on exchange rate expectations and on interest rates on publicly held government debt. In Italy, the high stock of such debt in relation to base money implies that, to offset the loss of seignorage, it will take only about a 1/2-percentage-point decline in real interest rates. A decline of this magnitude seems feasible, provided that there is credible action to place the public debt on a sustainable path.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet